MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN DAN PEMBAGIAN MENGGUNAKAN MULTIMEDIA INTERAKTIF BERBASIS MULTISENSORIS PADA SISWA BERKESULITAN BELAJAR - Mahilda Dea Komalasari dan Bayu Pamungkas (Universitas PGRI Yogyakarta, 2019)
AbstractThis study aims to improve the understanding of grade 2 students of Yogyakarta Karanganyar State Elementary School towards the concept of multiplication and division using multisensory-based interactive multimedia.The type of research used is classroom action research, with research subjects of grade 2 students of SDN Karanganyar Yogyakarta with a total of 11 students. This research was carried out in two cycles. Each cycle consists of one meeting. Data collection techniques use observation and tests. The research data was analyzed with quantitative descriptive techniques to analyze the results of the tests and qualitative descriptive to analyze the observations.The results showed that multisensory-based interactive multimedia can improve students' understanding of grade 2 SDN Karanganyar Yogyakarta on the concept of multiplication and division. This was indicated by an increase in the number of students who achieved the Minimum Completion Criteria (KKM) and an increase in the average test score. The number of students who reached the KKM in the pre-test was 0.09%, the end of the first cycle was 27.27%, and the end of the second cycle was (90.91%) reached the KKM, while the average score of the test before the action was 62.55, the end of the first cycle was 63.09, and end of cycle II is 85.54.Keywords: interactive multimedia, multisensoris, multiplication, division